Big effects of small nanoparticles on hydrophobically modified polyacrylamide in an aqueous solution. Issue 16 (24th December 2018) - Peng, Fangfang; Ke, Yangchuan; He, Jing; Lu, Shichao; Hu, Xu
ABSTRACT: In this study, we investigated the self‐assembly properties of small‐sized (3–5 nm) oppositely charged SiO2 nanoparticles (NPs) and hydrophobically modified polyacrylamide (hm‐PAM) in aqueous solutions by rheological and structural analysis. The results show that the addition of small NPs to the hm‐PAM solution remarkably enhanced its viscosity and viscoelasticity, and the viscosity remained high at elevated temperatures. Specifically, the low shear rate viscosity of the NP–hm‐PAM solutions increased by up to three orders of magnitude at a very low loading of NPs (10 −2 wt %). Moreover, there appeared to be no sediment in the dispersed system after over 18 months of storage. Scanning electron microscopy and transmission electron microscopy measurements indicated that additional physical crosslinks were formed after the addition of the small silica NPs to the hm‐PAM solutions. With the experiments and published results combined, we proposed a simple model of electrostatic and hydrophobic interactions for the crosslinking structure of the NP–hm‐PAM composite. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47269. Abstract :